ANALISIS LETAK LESI INSULA TERHADAP FUNGSI MOTORIK PASIEN STROKE ISKEMIK AKUT - Elta Diah Pasmanasari, Dwi Pudjonarko, Hermina Sukmaningtyas (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION MOST OF THE STROKE ISCHEMIC PATIENTS SUFFER FROM MOTOR DEFICIT THERE ARE SOME PARTS IN HUMAN BRAIN THAT CONNECTED TO MOTOR FUNCTION SUCH AS INSULA WHICH ONE OF ITS PROJECTION IS TO THE SUPPLEMENTARY MOTOR AREA INSULAR LESION IS ASSOCIATED WITH MOTOR DEFICIT IN STROKE ISCHEMIC PATIENTS